From occultism to hybrid Sufism: the transformation of an Islamic-hybrid spiritual group in contemporary Indonesia - Muttaqin, Ahmad (State Institute of Islamic Studies (STAIN) Salatiga, 2014)
This paper discuses transformation of an Islamic-Hybrid Spiritual group, theBhakti Nusantara (literally means âdevotion to nationâ), from spiritualitas kasar[rough spirituality] of occult-based spirituality to the finer spirituality [spiritualitasalus] which is linked to Sufi spiritual practices. Based on my field work inYogyakarta, in 2009 and 2010, the paper explains sociological context of groupâsinstitutional and spiritual transformation amid contemporary Islamic revivaland modernizing process of the country. It then argues that the transformationof the group was driven by the logic for presenting spiritual heritages thatare practically appropriate for modern life and which also fit religiously withorthodox Islam. Both the institutional transformation and the change of spiritualorientation of the group mark BN, as a hybrid spiritual group, to activelyinvolve in the opportunities of modernity, instead of resisting the challengesand pressures of modern life.Tulisan ini membahas proses transformasi dalam sebuah kelompok spiritualitashybrida bernama Bhakti Nusantara (BN) dari âspiritualitas kasarâ yang terkait dengan praktik klenik-kejawen ke spiritualitas halus yang berbasis pada praktiftasawuf/Sufisme. Berdasar hasil riset lapangan di Yogyakarta tahun 2009 dan2010, paper ini mencoba mengungkap konteks sosiologis dari transformasikelembagaan maupun perubahan orientasi spiritualnya di tengah prosesmodernisasi dan kebangkitan Islam di Indonesia pasca reformasi. Transformasidari spiritualitas kasar ke spiritualitas halus ini terjadi, diantaranya, dilatarioleh nalar untuk menyesuaiakn praktik dan layanan spiritual agar lebih sesuaidengan alam pikiran dan kebutuhan manusia modern dan praktik spiritualyang tidak bertentangan dengan ortodoksi keberagaan umat Islam. Transformasiyang terjadi di BN telah mengantarkan kelompok spiritualitas hibrida ini untukmenawarakan formula spiritual yang lebih pro aktif dalam menyongsong peluangyang ditawarkan modernitas, bukan formula spiritualitas untuk melawantantangan dan menghidnari tekanan kehidupan modern.